From ingestion to colonization: the influence of the host environment on regulation of the LEE encoded type III secretion system in enterohaemorrhagic Escherichia coli - Connolly, James P. R.; Finlay, B. Brett; Roe, Andrew J. (Frontiers in Microbiology, 2015)
Enterohaemorrhagic Escherichia coli (EHEC) binds to host tissue and intimately attaches to intestinal cells using a dedicated type III secretion system (T3SS). This complex multi-protein organelle is encoded within a large pathogenicity island called the locus of enterocyte effacement (LEE), which is subject to extensive regulatory control. Over the past 15 years we have gained a wealth of knowledge concerning how the LEE is regulated transcriptionally by specific, global and phage encoded regulators, but more recently, significant advances have been made in our understanding of how specific signals, including host or microbiota derived metabolic products and various nutrient sources, can affect how the LEE encoded T3SS is regulated. In this review we discuss transcriptional regulation of the LEE in EHEC, focusing on how these physiologically relevant signals are sensed and how they affect the expression of this major virulence factor. The implications for understanding the disease process by specific regulatory mechanisms are also discussed.